The inhibition of mirror generalization of letters in school-aged children - Resque, Deusa Priscila da Silva; de Moura Lobato, Adriany Maria; da Silva, Carolina Gomes; da Cruz Filho, Daniel Alves; da Fonseca, Susanne Suely Santos; de Oliveira Matos, Felipe; Pereira, Antonio (Frontiers in Psychology, 2023)
Gender differences in spatial abilities favor males in both childhood and adulthood. During early development, this discrepancy can be attributed, among other things, to the influence of an early testosterone surge in boys, societal stereotypes, and expectations about gender. In the present work, we created a spatial task (including letter rotation and letter mirroring) which used letters as stimuli and evaluated the performance of school-aged children (6-10 years old). During this age period, children are being taught literacy skills which rely on the reorganization of cortical networks and the breakdown of mirror generalization. We divided our sample (N=142, 73 females) into two age groups: 1st-2nd (literacy acquisition) (N=70, 33 females) and 3rd-5th (literacy consolidation) (N=72, 40 females) graders. While boys performed significantly better in letter rotation in the older group, girls’ performance was similar in both groups. This pattern is reversed for the mirror task, with older girls outperforming their younger counterparts and boys having similar performance in the two groups. Since the age period of our sample is not associated with large variations in the levels of reproductive steroids, we propose that the similarity of performance between younger and older girls in mental rotation of letters could be associated with society’s traditional attitudes and expectations on the relationship between visual spatial skills and gender. As for the mirror task, while only girls had a significant difference between the two age groups, boys did show an improvement, as expected for the inhibition of mirror generalization for letters during reading acquisition.